THE INFLUENCE OF LEARNING ENVIRONMENT ON MOTIVATION AND INTEREST IN PARTICIPATING ONLINE LEARNING DURING COVID-19 PANDEMIC IN GEOGRAPHY STUDENTS OF LAMPUNG UNIVERSITY - Julia Maharesti; Pargito Pargito; Listumbinang Halengkara (Journal Learning Geography, 2022)
The Covid-19 pandemic has changed the existing education system in Indonesia, including at the level of universities, especially the Geography Education Study Program of the University of Lampung. Learning that was originally carried out face-to-face turned into online (in-network). The purpose of this study is to find out the influence of the student learning environment on motivation and interest in participating during the Covid-19 pandemic in Geography students of the University of Lampung. The methods used in this study are descriptive methods with correlation design. The sample in the study was 67 respondents with questionnaire data collection techniques and documentation. The tool to analyze the data in this study used SPSS version 22. The results showed that there is an influence of the learning environment on online learning constraints with a large percentage of influence of 44.1% with independent variable indicators (X) namely: family environment and campus environment, while for dependent variables (Y) namely: learning motivation and student learning interests